IMPLEMENTASI SISTEM PENJAMINAN MUTU PENDIDIKANDI SMPN 22 PADANG - Azan Muhammad Akbar; Irfan Prima Bakti; Syahril Syahril; Irsyad Irsyad; Novriyanti Achyar (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to understand the education policies and the steps for ensuring the quality of education at SMPN 22 Padang. This research uses a qualitative approach. The type of research is a case study (single case study). The research subjects consisted of 15 informants selected purposively by considering their direct involvement in the implementation of education quality assurance at the school. Data collection techniques were carried out through in-depth interviews, observation, and documentation study. Data analysis was conducted interactively, involving stages of data reduction, data presentation, and drawing conclusions and verification. The research was conducted at SMPN 22 Padang, located at Jl. Tut Wuri Siteba, Nanggalo District, Padang City, West Sumatra. The conclusions of the study are as follows: 1) The education quality policy at SMPN 22 Padang refers to the eight National Education Standards, focusing on three National Education Standards, namely the Process Standard, Graduate Competency Standards and Facilities and Infrastructure Standards. 2) The steps in educational quality assurance consist of five stages: Quality Mapping, Preparation of Fulfillment Plans, Quality Implementation, Quality Evaluation, and Standard Setting.